IMPROVING READING ABILITY OF CLASS II STUDENTS ELEMENTARY SCHOOL TIPAR IN LEARNING LANGUAGE ABILITIES THROUGH IMAGE MEDIA - Tati Nurhayati (JLER (Journal of Language Education Research), 2021)
This study aims to explain about learning to read beginners using picture media classically and in groups and the process of increasing students' reading skills. Achieve this goal, classroom action research was conducted, with assistance of classroom teachers and 30 students of SDN TIPAR. Research data obtained by qualitative methods, observation and assisted by a recording aid in form of a camera. This research was conducted with two cycles of action. First cycle tends to increase participation and reading ability in word card and picture matching games. and the second cycle on reading improvement. Each cycle consists of stages: preparation, action, action, observation, analysis and reflection. The results of this study indicate that learning to read beginning with picture media classically students who lack courage tend to be passive so that when teacher assigns students to match word cards with pictures the students do not want to and the attention of some students is less focused in this learning and their reading ability is still dominated by active students. Learning the ability to read using picture media in groups, students are invited to play a game of matching word cards with pictures and their own friends and teacher acts as a facilitator and motivator. Student creativity, student shyness can be overcome and students' reading ability can be improved and the learning atmosphere is more attractive.